Wire and arc additive manufacturing of HSLA steel: Effect of thermal cycles on microstructure and mechanical properties - Rodrigues, Tiago A.; Duarte, V.; Avila, Julian A. [UNESP]; Santos, Telmo G.; Miranda, R. M.; Oliveira, J. P. (Elsevier, 2019)
Wire and arc additive manufacturing (WAAM) is a viable technique for the manufacture of large and complex dedicated parts used in structural applications. High-strength low-alloy (HSLA) steels are well-known for their applications in the tool and die industries and as power-plant components. The microstructure and mechanical properties of the as-built parts are investigated, and are correlated with the thermal cycles involved in the process. The heat input is found to affect the cooling rates, interlayer temperatures, and residence times in the 800–500 °C interval when measured using an infrared camera. The microstructural characterization performed by scanning electron microscopy reveals that the microstructural constituents of the sample remain unchanged. i.e., the same microstructural constituents—ferrite, bainite, martensite, and retained austenite are present for all heat inputs. Electron backscattered diffraction analysis shows that no preferential texture has been developed in the samples. Because of the homogeneity in the microstructural features of the as-built parts, the mechanical properties of the as-built parts are found to be nearly isotropic. Mechanical testing of samples shows excellent ductility and high mechanical strength. This is the first study elucidating on the effect of thermal cycles on the microstructure and mechanical properties during WAAM of HSLA steel.
Keywords: Additive manufacturing; High-strength low-alloy steels; Mechanical properties; Microstructure characterization; Wire and arc additive manufacturing